HOUSE DESIGN PRINCIPLE TO HELPS THE DWELLERS ACHIEVE MINDFULNESS TO MINIMIZE COVID-19’S PSYCHOLOGICAL IMPACT. - Purnaumbara, Kartiansmara Lilih (Border: Jurnal Arsitektur, 2021)
Pandemic COVID-19 causing various negative impact towards the society. Not only physical health problems, mental health problems are also significally increased during pandemic, while anxiety disorder appears to be frontliners among all of mental health problem during pandemic. In an anxiety disorder treatment, psychologist are familiar with series of training to help patient achieve mindfulness, and as a result, help patient to deal with the anxiety disorder. The research purposes are to formulate basic house design principles to helps the dwellers achieve mindfulness, as an architectural design response to deal with COVID-19 pandemic, and minimize COVID-19’s negative impact through preventive and restorative measure. This research are being conducted through literature review method, through a wide-ranging literature from a book and research report that already been published in a scientific journal. The principles are then being examined through a elimination process to formulate an operational design principle in architecture. The result from the elaboration conclude that house design must apply a certain design element to create positive stimulus and engage the senses of the dwellers, the spatial arrangement should be functionally flexible, and the spatial arrangement of the house are also need to be sequentially arranged to make the dweller experience various spatial experience provided by the house design.